Painful and painless ophthalmoplegia with cavernous sinus pseudotumour. Issue 3 (September 1996) - Ganesan, V; Lin, J P; Chong, W K; Kirkham, F J; Surtees, R A
Abstract : Acquired isolated ophthalmoplegia in childhood has many potential causes. Although other ophthalmological or clinical features may aid lesion localisation, the absence of these does not preclude structural pathology. Two cases of cavernous sinus pseudotumour presented as ophthalmoplegia with and without pain. Magnetic resonance imaging of the cavernous sinus revealed the presence of enhancing tissue consistent in appearance with pseudotumour in both cases, and they responded well to steroid treatment. These cases emphasise the importance of detailed imaging of the cavernous sinus in the investigation of these symptoms in order to exclude this treatable condition.